Drugs, the brain, and behavior : the pharmacology of drug use disorders - Brick, John, 1950- (Routledge, 2013)
"Drugs, the Brain, and Behavior uses a balance of instruction, illustrations, and tables and formulas that will give you a broad, lasting introduction to this intriguing subject. Whether you're a nurse, chemical dependency counselor, psychologist, or clinician, this book will be a quick reference guide long after the first reading"--